(untitled) (International Journal of Irrigation and Water Management, 2013)
A field experiment was conducted to study the efficacy of deficit irrigation on litchi crop under two deficit irrigation (DI) strategies viz. reducing the quantity applied (Quantitative Deficit) and prolonging the period without irrigation (Temporal Deficit). Under quantitative deficit water was applied at 60, 40 and 20 % of ETc, where ETc is crop evapotranspiration. Temporal deficit was achieved through different irrigation start times viz. from 1stFebruary (pre flowering), 1stMarch (start of fruiting) and 1stApril (start of fruit development stage). Results showed that comparable litchi yields can be obtained even with deficit irrigation. Drip irrigation system recorded highest fruit weight (22.6 g) at 60 % ETc and irrigation starting from 1stMarch. The prolonged moisture stress between two irrigations under basin system resulted in lowest fruit length, smallest fruit diameter and higher fruit cracking percentage. Deficit water application under drip system resulted in higher reducing sugar content (7.5 %) of litchi fruits. Highest IWUE (57.1 g/m3) was observed in case of drip irrigation having 20 % ETc level and irrigation starting from 1stApril. Deficit irrigation showed great potential to increase the irrigation water use efficiency of litchi production with slight deviation in potential yield.